Penilaian Kesehatan KJKS BMT Binamas - Adi Angga Sukmana; Sri Mulyati (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2015)
The analysis conducted will interpret ratios or financial data and its implications. Thisresearch is compiled to analyze health assessment KJKS BMT Binamas years 2012-2014 using a standard assessment of the Regulation of the Minister of State forCooperatives and SMEs RI Number: 35.3 / Per / M.KUKM / X / 2007 on guidelinesfor a health assessment KJKS and UJKS Cooperative. The results of this study will betaken into consideration in the evaluation and a policy for BMT KJKS Binamas toimprove their business performance so that stability is maintained and is expected toenhance public trust in this Islamic Microfinance Institutions. The approach used inthis study is a quantitative and descriptive variables used are capital; asset quality;management; efficiency; liquidity; independence and growth; the identity of thecooperative; and compliance with Islamic principles. Based on analysis of the healthassessment KJKS BMT Binamas can be seen that score recapitulation of eightvariables in 2012 amounted to 74.92% so that it can be categorized fairly sound, andin 2013 increased to 74.92% with the category Fairly Healthy, later in 2014 slightlydecreased to 75.95% are still in the category of Fit. Value ratios consistently ratedhigh happens because KJKS continue to maintain sound operational